Implementasi Manajemen Strategis pada Program School Improvement - Fauzi, Farid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Madrasa quality improvement is a crucial thing in the progress of Islamic education in Indonesia. School Improvement is a program that works to improve the quality of madrasas, especially at MTsS Maqama Mahmuda. The purpose of this study was to determine the description of the strategic management process that occurred at MTsS Maqama Mahmuda from the school improvement program. The form of this research is descriptive qualitative with the subject of the study consisting of the chairman of the foundation, the head of the madrasa, the teaching staff, the teaching staff and one parent of the santri. The data used in this study are primary data that is the result of non-participatory observation and in-depth interviews and secondary data, which are documents that support this research. Based on the research results, several research findings can be found, including: 1) There is an analysis of the internal and external environment of madrasas in preparing strategic plans in the School Improvement Program 2) Formulation and reformulation of strategic planning by considering risk management 3) Implementation of effective strategic management through commitment and consistency from educators and education staff 3) Effective control and evaluation system by prioritizing the principle of rigor, transparency, accountability and sustainability. So it can be concluded that through the implementation of effective and efficient strategic management at MTsS Maqama Mahmuda has produced good performance from the School Improvement Program.Â